Identifying problems for choosing suitable areas for installation of a new landfill through GIS technology: A case study - Nascimento, Victor Fernandez; Silva, Alexandre Marco da [UNESP] (Taylor & Francis Inc, 2014)
Selecting a suitable place to install a new landfill is a hard work. Bauru is a Brazilian municipality where the local landfill currently in use has a life span that is almost over, and the selection of a new area for a future landfill is crucial and urgent. Here we use a geographic information system (GIS) approach to indicate possible suitable areas for installing the landfill. The considered criteria were: river network and the respective buffer zone, relief, urban areas and their respective buffer zone, existence of Areas for Environmental Protection (AEPs), occurrence of wells and their respective buffer zones, existence of airports and their buffer zones, wind direction, and the road network and its respective buffer zone. Due the facts that (1) Bauru has an urban area relatively large in relation to whole municipal area, (2) Bauru has two airports, and (3) this area encompasses parts of three AEPs, the model showed that there are few areas suitable and moderately suitable in Bauru, and the greater part of the municipality is unsuitable to install a new landfill. Due to this important finding reported here, the local policymakers should consider the suitable or even moderately suitable areas for analysis in situ or look for other creative solutions for destination of the solid waste. We highly encourage the use of GIS in studies that seek suitable areas for future landfills, having found that SIG was a tool that allowed fast and precise work and generated an outcome sufficiently clear of interpretation.Implications: Solid waste (SW) management is one of the main environmental concerns nowadays. Landfilling SW is still the main practice to disposal of such material. However, for many regions, suitable places for landfilling are getting scarce. This study proved this situation for a populous place in a southeastern Brazilian region. This study also showed how the decision makers should manage the problem in order to minimize the amount of SW generated and delivered for the landfill. Massive investment in education is a critical issue to reach the proposed aim.